2017
DOI: 10.3390/catal7070194
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Carbonation Carbon-Coated CdS Nanocomposite with Enhanced Photocatalytic Activity and Stability

Abstract: Herein, a novel CdS nanocomposite is fabricated by a facile one-pot hydrothermal method assisted by glucose and polyvinylpyrrolidone (PVP). The as-prepared CdS is coated with a thin layer, which is determined to be hydrothermal carbonation carbon (HTCC) mainly containing semiconductive polyfuran. The as-prepared HTCC-coated CdS shows superior photocatalytic activity for the degradation of Rhodamine B (RhB) under visible light irradiation (λ ≥ 420 nm). The optimum sample (glucose content of 0.1 g) shows a degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The BET surface area of the CdS NRs was calculated as 51 m 2 /g. The higher surface area of the as-synthesized CdS NRs photocatalyst compared to the reported CdS photocatalyst [37] makes the transfer of photo-generated charges easier due to the higher number of available active sites on the surface, resulting in improved photocatalytic performance. The average pore size was calculated as 32.7 nm.…”
Section: Structural Chemical and Optical Analysis Of Cds Nrsmentioning
confidence: 99%
“…The BET surface area of the CdS NRs was calculated as 51 m 2 /g. The higher surface area of the as-synthesized CdS NRs photocatalyst compared to the reported CdS photocatalyst [37] makes the transfer of photo-generated charges easier due to the higher number of available active sites on the surface, resulting in improved photocatalytic performance. The average pore size was calculated as 32.7 nm.…”
Section: Structural Chemical and Optical Analysis Of Cds Nrsmentioning
confidence: 99%
“…Cadmium sulfide (CdS) is a semiconductor with a suitable band gap for the efficient use of solar energy and has received enormous research attention in environmental remediation through visible-light-driven photocatalysis . Specifically, the photocatalytic activity and stability of composite CdS were enhanced greatly in organic pollutant degradation supported by carbon materials derived from organic matter. It was found that a biochar carrier did not only prevent catalyst deactivation, particle aggregation, and photocorrosion, but also facilitated the transport and contact of organic substrates between the support and the catalytically active sites. ,, In light of these advantages, specific research has focused on the fabrication of practically applicable photocatalysts by using low-cost and functionally optimized carbon materials as a catalyst carrier. ,, Although the biomass of Cd hyperaccumulators contains high levels of Cd (>0.7%, dry weight), the biomass can be constantly recycled in the form of biochar after detoxification . However, to date, no research has been conducted to find a feasible method for recycling the Cd-enriched biomass into a composite CdS photocatalyst, which could achieve high-value utilization of Cd-enriched hyperaccumulator biomass to balance the advantages of phytoremediation and the disadvantages of the potential secondary pollution risk of hazardous hyperaccumulator biomass.…”
Section: Introductionmentioning
confidence: 99%
“…Different synthesis methods of HTC were considered [32][33][34]. e preparation of biomass porous carbon usually requires a high temperature calcination process [21][22][23], while our hydrothermal carbon (HTC) is prepared by a one-step hydrothermal method, which is much simpler.…”
Section: Synthesis Of Htcmentioning
confidence: 99%